Violence against Women: An Analysis of the Infirmed Legal System of Pakistan - Siddique, Marriyam; Hussain Shah, Syed Sibtain (Journal of Public Policy Practitioners, 2023)
In Pakistan, a woman's life is governed by the rigid norms of her extended family, faith, and tribal community. This paper aims to investigate the philosophy behind gender-based violence, particularly the violence against women and its related customary practices in different areas in Pakistan, in the backdrop of the infirmed legal system of the country. The authors employ descriptive method to scientifically address the concerned issue. The theory of social change, which broadly focuses on the problem, is additionally significant to probe the violence against women in Pakistan. Throughout the country, women are subjected to a wide range of detrimental customs, including forced marriages, religious conversions, and the exchange of women in marriage without their consent. This study looks into why gender-based violence persists in Pakistan, despite the establishment of the state in the name of Islam, a religion that emphasizes women’s equality and respect in the society. By examining all relevant aspects, the study concludes that customary laws are dominant over state legislation in protecting women from violence. The study determines that Pakistan's legal system is flawed, with significant gaps that must be filled by well-structured legislation to ensure women's safety from abuse.